Effects of ZnO nanoparticles and its bulk form on growth, antioxidant defense system and expression of oxidative stress related genes in Hordeum vulgare L. (January 2022) - Azarin, Kirill; Usatov, Alexander; Minkina, Tatiana; Plotnikov, Andrey; Kasyanova, Alexandra; Fedorenko, Aleksei; Duplii, Nadezhda; Vechkanov, Evgeniy; Rajput, Vishnu D.; Mandzhieva, Saglara; Alamri, Saud
Abstract: A comparative analysis of physio-biochemical indices and transcriptional activity of oxidative stress genes in barley ( Hordeum vulgare L.) seedlings after 7-days exposure to bulk- and nano-ZnO (300 and 2000 mg/L) was carried out. A dose-dependent reduction in the length and weight of roots and shoots, as well as a significant accumulation of Zn in plant parts, was shown. Alterations in the shape and size of organelles, cytoplasmic vacuolization, and chloroplast and mitochondrial disorganization were also revealed. These processes are particularly pronounced when H. vulgare is exposed to the higher concentrations of nano-ZnO. The study of the antioxidant defense system revealed mainly an increase in the level of reduced glutathione and the activities of superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), and glutathione S-transferase (GST). The increases in activity, by 4-fold and 3-fold, was found for glutathione transferase in the roots when exposed to 2000 mg/L bulk- and nano-ZnO, respectively. The study of transcriptional activity demonstrated that in the roots under the influence of bulk- and nano-ZnO, along with Mn-SOD, Fe-SOD is highly expressed, mainly associated with the protection of chloroplasts. Analysis of the Cat 1 and Cat 2 gene expression showed that the main contribution to the increase in catalase activity in treated H. vulgare is made by the CAT-1 isozyme. Generally, in response to the impact of the studied ZnO forms, the antioxidant defense system is activated in H. vulgare, which effectively prevents the progression of oxidative stress in early stages of plant ontogenesis. Nevertheless, with constant exposure to bulk- and nano-ZnO at high concentrations, such activation leads to a depletion of the plant's energy resources, which negatively affects its growth and development. The results obtained could be useful in predicting the risks associated with the further transfer of nano-ZnO to the environment. Highlights: Dose-dependent phytotoxicity was observed in bulk- and nano-ZnO treated barley plants. Nano-ZnO as and its bulk form induced antioxidant system activation. Isoforms of the same antioxidant enzyme had different transcription level changes after treatment.